China and Arctic energy: drivers and limitations. Issue 2 (2nd July 2016) - Weidacher Hsiung, Christopher
Abstract: China's growing demand for oil and gas is forcing the country to look abroad to secure new sources of imports. The Arctic region, rich in oil and gas resources, could function as such a source, and Chinese oil companies have already started to engage in oil and gas exploration and production there. The literature has tended to take this as evidence that China will become an increasingly active and important player in Arctic oil and gas resource developments, and the sanctions imposed on Russia's energy sector by the USA and the EU following the Russian annexation of Crimea are seen as further opening up possibilities for greater Chinese participation. This article, however, argues that China's Arctic oil and gas interests are in fact modest. Domestic views on Chinese involvement in Arctic gas and resource development have been mixed and cautious, indicating a wait-and-see approach. There have been few concrete Chinese investments further indicating limited interest. Only the onshore Yamal LNG project in the Russian Arctic can be characterised as substantial Chinese participation. Moreover, the challenges and high costs of oil and gas production in the Arctic, China's increased import options, the current economic slowdown in China and security developments in the Arctic region all impact China's motivations and possibilities for participation in the development of Arctic energy resources.